Proses Rehabilitasi Sosial Orang Dengan Gangguan Jiwa (ODGJ) Pasca Pasung di Unit Pelaksanaan Teknis Rehabilitasi Sosial Bina Laras Kediri - Hidayah, Bidayatul; Hendrijanto, Kris; Dewi Poerwanti, Sari; Santoso, Budhy; Nugroho Puspito, Agung (Pascasarjana Universitas Jember, 2023)
This study focuses on the social rehabilitation process of post-restraint patients at the Technical Implementation Unit for Social Rehabilitation Bina Laras (UPT RSBL) Kediri. In this research, a descriptive approach was employed with qualitative research methods. Data were collected through observation, interviews, and documentation and analyzed using Miles and Huberman's analytical method. The study revealed five stages of social rehabilitation: intake, assessment, the rehabilitation process, evaluation, and resocialization. During the assessment stage, patients are evaluated by social workers and medical professionals to determine their condition and the subsequent rehabilitation actions. Patients engage in various rehabilitation activities that encompass physical, mental, social, spiritual, skill, and artistic aspects. Evaluation is performed to assess patient progress, and they may repeat the rehabilitation phase if necessary. Recovered patients are prepared to return to their family environment. This research provides insights into UPT RSBL Kediri's efforts to assist post-restraint patients in restoring their social function and preparing them for reintegration into society.